2022
DOI: 10.20944/preprints202205.0355.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling of Energy and Exergy Efficiencies in High Vacuum Flat Plate Photovoltaic Thermal (PV-T) Collectors

Abstract: This work deals with the performance evaluation of novel flat photovoltaic-thermal (PV-T) modules under vacuum. Through a 1D (dimensional) steady-state-energy-balance numerical model developed in MATLAB, two different layouts are studied: the first consisting of a photovoltaic (PV) cell installed just below the glass encapsulating the flat panel, and the second where the PV cell is placed on the selective solar absorber (SSA). In both cases the thermal and electrical efficiencies have been evaluated at differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The goal is year-round heat generation at medium temperatures, where the main technological challenges lie, and efficient power generation. However, in [31] we demonstrated that layout B, rather than layout A, is the one that maximizes the conversion of solar energy to electrical+thermal energy, allowing the entire portion of the solar spectrum not converted to electricity by the PV layer to reach the SSA below (see in particular Figs. 1 and 7 in [31]).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The goal is year-round heat generation at medium temperatures, where the main technological challenges lie, and efficient power generation. However, in [31] we demonstrated that layout B, rather than layout A, is the one that maximizes the conversion of solar energy to electrical+thermal energy, allowing the entire portion of the solar spectrum not converted to electricity by the PV layer to reach the SSA below (see in particular Figs. 1 and 7 in [31]).…”
Section: Introductionmentioning
confidence: 89%
“…However, in [31] we demonstrated that layout B, rather than layout A, is the one that maximizes the conversion of solar energy to electrical+thermal energy, allowing the entire portion of the solar spectrum not converted to electricity by the PV layer to reach the SSA below (see in particular Figs. 1 and 7 in [31]). However, the previous model was developed by setting β=-0.2 %/K, limiting the description to a few real solar cells (mainly crystalline silicon cells).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation